Promoting Students’ English Vocabulary through Explicit Morphological Instructions and Exploring Students’ Perceptions - Asfi Aniuranti; Yasinta Wulandari; M.Happy Nur Tsani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2022)
This research aims to enhance students’ English vocabulary mastery through explicit morphological instructions as well as to investigate students’ perceptions of its usage during online learning. This research was a classroom action research consisting of two cycles. The researchers employed a test, observation sheet, and questionnaire to obtain the data. Furthermore, the data gathered was analysed using simple statistical analysis such as average score, percentage, and percentage enhancement. After implementing explicit morphological instructions, there was an enhancement in students’ vocabulary mastery. In cycle 1, the enhancement of the average score from pre-test to post-test was 7.9%. Therefore, the team concurred to conduct cycle 2. In cycle 2, the improvement of students’ vocabulary mastery achieved 27%. This percentage surpassed the success criteria of this action research (15%). Therefore, the team ended the action research. In addition, the students also responded to the usage of explicit morphological instructions positively. Most of the students agreed or strongly agreed with each item in the questionnaire. These results indicate positive responses. In short, explicit morphological instructions could promote students’ vocabulary mastery, and this strategy receives positive feedback from the students.